Enhancing Competitiveness in Indonesia's Furniture Craft Industry: A Five Porter Analysis - Sri Herliana; Qorri Aina; Umi Zuraida; Syifaya Qorina; Nur Lawiyah (AIBPM Publisher, 2023)
Indonesia's craft industry, encompassing traditional crafts such as batik printing, weaving, and furniture, plays a vital role in the nation's cultural identity. Micro, Small, and Medium-sized Enterprises (MSMEs) are key players, propelling the growth of creative cities. Among them, the furniture industry is prominent, despite a minor dip in 2022 exports. Notably, the United States accounts for 58.5% of Indonesian furniture exports and is the main export destination. This study employs the Five Porter Analysis to explore external factors influencing the furniture craft sector. The findings emphasize the importance of ensuring a stable supply of raw materials, aligning products with international preferences, promoting sustainable resource management, fostering innovation, and navigating international trade regulations. Government support is pivotal. The results demonstrate the need for a comprehensive strategy to sustain competitiveness. It calls for capacity building, market research, and global collaboration to strengthen Indonesia's position in the international market. This research offers valuable insights for policymakers, industry stakeholders, and MSMEs to enhance Indonesia's furniture craft industry's competitiveness while preserving its rich cultural heritage.